Immune functions of platelets - Duerschmied, Daniel; Bode, Christoph; Ahrens, Ingo (Thrombosis and Haemostasis, 2014)
This review collects evidence about immune and inflammatory functions of platelets from a clinician’s point of view. A focus on clinically relevant immune functions aims at stimulating further research, because the complexity of platelet immunity is incompletely understood and not yet translated into patient care. Platelets promote chronic inflammatory reactions (e.g. in atherosclerosis), modulate acute inflammatory disorders such as sepsis and other infections (participating in the host defense against pathogens), and contribute to exacerbations of autoimmune conditions (like asthma or arthritis). It would hence be obsolete to restrict a description of platelet functions to thrombosis and haemostasis – platelets clearly are the most abundant cells with immune functions in the circulation.
Keywords: Platelet immunology; sepsis; leukocyte function/activation